Prospects of Chemotherapy for Gastrointestential Stromal Colon Tumours - A. R. Mukhamediyarov; L. I. Bashirova; A. I. Maksyutova; A. T. Gattarova (Креативная хирургия и онкология)
Gastrointetinal stromal tumours are the most common primary mesenchymal tumours of the gastrointestinal tract. According to statistical data, the annual incidence of this pathology in Russia comprises 13 patients per 1 million inhabitants, i.e. about 2,000 patients per year on average. In the United States, 3,000–4,000 cases are registered every year. This article discusses general and specific issues associated with morbidity and mortality from gastrointestinal stromal tumours, as well as reasons for the low efficacy of surgical and targeted therapies. Methods for combined treatment of patients with gastrointestinal stromal tumours are proposed. The treatment of such pathologies has evolved with the development of immunohystochemical analytical procedures and therapies against KIT/PDGFRA-specific protooncogenes, as well as the emergence of low-molecular kinase inhibitors. However, the probability of non-recurrence survival can only be increased by complete surgical removal of gastrointestinal stromal colon tumours. In the surgical treatment, three main approaches are defined: the initial stage of treatment, provided that the tumour is resectable and has a small size; surgical treatment after neoadjuvant therapy; symptomatic treatment, so-called ‘debulking surgery’. Adjuvant targeted therapy with Imatinib provides for a high objective response. The use of Imatinib chemotherapy determines the efficacy and radicality of surgical treatment in most cases. In general, the question of treating gastrointestinal stromal colon tumours is still relevant, requiring further research and objective evaluation of all technical and tactical approaches in the context of distant results.